2016
DOI: 10.1155/2016/4670818
|View full text |Cite
|
Sign up to set email alerts
|

Appetite Suppression and Antiobesity Effect of a Botanical Composition Composed ofMorus alba,Yerba mate, andMagnolia officinalis

Abstract: Background. Obesity and its comorbidities continue to challenge the world at an alarming rate. Although the long term solution lies on lifestyle changes in the form of dieting and exercising, drug, medical food, or dietary supplement interventions are required for those who are already obese. Here we describe a standardized blend composed of extracts from three medicinal plants: Morus alba, Yerba mate, and Magnolia officinalis for appetite suppression and metabolic disorders management. Method. Extracts were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…There was also a reduction in appetite VAS measures, especially for hunger ( p = 0.019) and prospective eating ( p = 0.022), ( Table 1 ) following the YM ingestion compared with PLC. These YM appetite control effects are reported in humans for the first time, considering previous positive effects reported in animal models [ 13 , 14 ], and the recent report of appetite suppression following exercise in trained female participants [ 41 ]. The reduced VAS appetite scores are also in line with previous results found when YM was combined with other multi-ingredients before and after moderate exercise at Fatmax intensities at 43% , which is slightly higher than COP intensities of 38% to the present COP intensities [ 22 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…There was also a reduction in appetite VAS measures, especially for hunger ( p = 0.019) and prospective eating ( p = 0.022), ( Table 1 ) following the YM ingestion compared with PLC. These YM appetite control effects are reported in humans for the first time, considering previous positive effects reported in animal models [ 13 , 14 ], and the recent report of appetite suppression following exercise in trained female participants [ 41 ]. The reduced VAS appetite scores are also in line with previous results found when YM was combined with other multi-ingredients before and after moderate exercise at Fatmax intensities at 43% , which is slightly higher than COP intensities of 38% to the present COP intensities [ 22 ].…”
Section: Discussionmentioning
confidence: 56%
“…Recent findings have also indicated that YM metabolic properties may be combined with positive psychomotor and appetite control effects, which complement the YM fat-loss promoting properties. Such effects include suppressed appetite through an increased expression of glucagon-like peptide-1 (GLP-1) and delayed gastric emptying, as seen in mice studies [ 12 , 13 ], and increased ghrelin up to 4.2-fold in rat models following YM ingestion [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The feed intake was monitored for three days to determine the average daily intake of each rat. 18 Thereafter, vehicle, naltrexone or chrysin was administered to the rats and the feed intake was monitored for the next 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Other plants also regulated the serum lipid profiles, including TG, TC, ALT, AST and ALP concentration and expression of the transcription factors responsible for lipid metabolism. C57BL/6J mice were also implemented as an experimental model for Nelumbo nucifera [ 81 ], chlorogenic acid [ 82 ], Capsicum annuum [ 83 ], Cudrania tricuspidate [ 84 ], Morus alba , Ilex paraguariensis , Rosmarinus officinalis , Moringa officinalis [ 85 , 86 ], Ecklonia cava [ 47 ], Cirsium cetidens [ 87 ], Gymnema sylvestre [ 88 ] and Ishige okamurae [ 89 ], and among all these plants, the mixed extracts of Morus alba , Ilex paraguariensis and Rosmarinus officinalis showed the maximum anti-obesity effect as it decreased the body weight and relative weight of other body organs up to 98% and regulated the serum lipid profile by decreasing the TC (18.6%), LDL-c (59%), ALT (60.1%), AST (35.2%), insulin (75.9%) and leptin (46.8%). These results are maximum among the plants described above in Table 1 on C57BL/6J mice.…”
Section: Anti-obesity Effects Of Different Plant Resourcesmentioning
confidence: 99%